Compensability index for compensation radiotherapy after treatment interruptions. - Putora, Paul Martin; Schmuecking, Michael; Aebersold, Daniel; Plasswilm, Ludwig (Radiation Oncology, 2012)
Background: The goal of our work was to develop a simple method to evaluate a compensation treatment after unplanned treatment interruptions with respect to their tumour- and normal tissue effect.Methods: We developed a software tool in java programming language based on existing recommendations to compensate for treatment interruptions. In order to express and visualize the deviations from the originally planned tumour and normal tissue effects we defined the compensability index.Results: The compensability index represents an evaluation of the suitability of compensatory radiotherapy in a single number based on the number of days used for compensation and the preference of preserving the originally planned tumour effect or not exceeding the originally planned normal tissue effect. An automated tool provides a method for quick evaluation of compensation treatments.Conclusions: The compensability index calculation may serve as a decision support system based on existing and established recommendations.